Response of endophyte-infected and endophyte-free tall fescue plants to partial submergence at two developmental stages - Petigrosso, Lucas R. (2024)
Tall fescue (Festuca arundinacea Schreb.) is a perennial C3 grass species usually associated with the endophyte fungus Epichloë coenophiala that enhances tolerance to biotic and abiotic stresses. Given that the proportion of infected tall fescue plants in the grasslands of the Flooding Pampa (Argentina) has been progressively increasing, it is proposed that endophytes confer tolerance to the stresses characteristic of that environment, especially flooding. Plants from a naturalized population and a commercial cultivar were grown, both with and without endophyte (wild type and AR584 respectively). The plants were subjected to two submergence treatments (i.e., control and partial submergence) in two development stages (5-leaf stage and beginning of the elongation of internodes). Plant performance (aerial and root biomass, root aerenchyma formation, total root length and root diameter, proportion of reproductive tillers, number of panicles and seeds produced) and endophyte transmission to progeny were evaluated. Endophytes did not alter the ecological fitness of plants under partial submergence. Independently of the water condition, the symbiosis was linked to low biomass in plants from the naturalized population, while the opposite occurred in plants from the cultivar. Partial submergence did not affect the germination of the seeds produced, nor the transmission of the endophyte to the seedlings that originated from them. Our work suggests that the invasion ability of tall fescue in the Flooding Pampa grasslands is not related to an endophyte-mediated improvement of plants to tolerate water excess.